Spiritualitas Sains Modern: Pembacaan Terhadap Relasi Agama dan Sains - Mishbah Khoiruddin Zuhri (JURNAL PENELITIAN, 2017)
Modern science receives diverse responses from religionists. This is motivated by the reading of religious texts, which are often considered contrary to recent scientific research. The advancement of modern science is not connected with improvements in spirituality. Spirituality becomes another dimension of science. In that situation, the integration theory of Ian G. Barbour attempts to unravel the patterns of the relationship between modern science and religion. There are four types of relationships: conflict, independence, dialogue, and integration. This approach is rarely implemented in the realm of Islamic studies. This research seeks to implement the approach in Islamic studies by using a descriptive-analytical method. The authors found that the tendency of Muslim scientists is more dominant in the exploration of Islamic studies than in the scientific aspect. Therefore, the dominant relationship between science and religion is conflict, dialogue, and natural theology. The contributing factors are the educational background of Muslim scientists, which is predominantly in religious studies; the limitations of interdisciplinary studies; and the lack of openness and renewal of views (tajdīd) on religious texts.